A Healthy Divide: Subgroups as a Stimulus for Team Learning Behavior - Gibson, Cristina; Vermeulen, Freek (Administrative Science Quarterly, 2003)
This paper examines the relationship between subgroups and team learning behavior, defined as a cycle of experimentation, reflective communication, and codification. We develop the construct of “subgroup strength,” defined as the degree of overlap across multiple demographic characteristics among a subset of team members. Contrary to conventional wisdom, we propose that the presence of subgroups within a team may stimulate learning behavior and that organizational design features, such as performance management by an external leader, team empowerment, and the availability of a knowledge management system, may have different effects on teams, depending on subgroup strength. Data on 156 teams in five pharmaceutical and medical products firms confirmed that moderately strong demographic subgroups in teams fostered learning behavior. In addition, both very homogeneous and very heterogeneous teams were more inclined to engage in learning behavior, but only if we controlled for the concurrent effect of subgroup strength. Finally, subgroup strength moderated the impact of organizational design features on team learning. Overall, this study contributes to the literature on team composition, design, and learning by highlighting the importance of subgroups for understanding team behavior.